Pendampingan Baca Tulis bagi Siswa Kelas 1 yang Mengalami Kesulitan Membaca dan Menulis di UPTD SDN Dharma Camplong 3 - Wardatul Laily, Adelia (Al-Khidmah: Jurnal Pengabdian Kepada Masyarakat, 2025)
Early reading and writing skills (MMP) serve as a crucial foundation for students’ academic success at subsequent educational levels. However, initial observations at UPTD SDN Dharma Camplong 3 identified a number of first-grade students who experienced significant difficulties in mastering these basic skills, potentially hindering their overall learning development. This community service activity aims to provide a structured intervention through an intensive mentoring program to improve the literacy skills of students experiencing such difficulties.The method employed is Classroom Action Research (CAR) with a one-group pretest–posttest design involving 10 first-grade students. The intervention was conducted over a two-month period using an individual and multisensory approach, integrating various methods such as phonics, syllables, Structural Analytic Synthetic (SAS), and diverse learning media. Evaluation was carried out by comparing pre-test and post-test results. The findings revealed a significant improvement in students’ literacy skills. The average score increased from 45% in the pre-test to 75% in the post-test. The success of this program is attributed to the individual diagnostic approach, consistent mentoring intensity, effective multisensory methods, and the creation of a positive and motivating learning environment. It is concluded that intensive and individualized mentoring programs are an effective strategy to overcome early literacy difficulties (MMP) among first-grade students.